Development of Scientific Literacy-Based Modules on Class XI Regulation System Material at SMA Yayasan Nurul Islam Indonesia - Pristika Ningsih; Kartika Manalu; Rohani Rohani (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine students' responses to scientific literacy-based modules on regulatory system material and to determine the feasibility of scientific literacy-based modules on regulatory system material. The product development design uses the Borg & Gall model with eight stages including, potentials and problems, data collection, product design, product validation, product revision, product testing, product revision, and the final product. This research was carried out from September to December 2021 with a research sample of 35 students in class XI SMA Yayasan Nurul Islam Indonesia. The results of this study showed that the percentage met the very feasible category with the acquisition of an average score on each aspect, namely 83% by material experts, 92% by media experts, 92% by biology teachers and 93% by students. So it can be concluded that scientific literacy-based module teaching materials are very feasible to use for teaching and learning activities.